(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kazanghy I. The competent approach in the professional training of future elementary school teachers. The article is devoted to the meaning of a competent approach in the future specialists’ training under the conditions of Euro Integration process; the components of school teachers’ professional educative competence are described here.